CONTRIBUTION OF PHARMACIES AND PHARMACISTS TO LOCAL ECONOMIC GROWTH AND CONTROL OF PUBLIC HEALTH COSTS - Gunawan Widjaja; Dyah Ersita Yustanti; Rio Johan Putra (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Pharmacies and pharmacists play a strategic role in supporting health development while contributing to local economic growth. This study aims to analyse the contribution of pharmacies and pharmacists to the local economy and their efforts in controlling public health costs. Through literature review and descriptive approach, it was found that pharmacies not only provide access to medicines and health services but also create jobs, support micro and small businesses, and increase the income of the surrounding community. On the other hand, pharmacists play a role in educating the public about rational drug use, promoting the use of generic drugs, and conducting efficient patient therapy management. These roles have proven to reduce healthcare costs at both the individual and national levels. Thus, pharmacies and pharmacists not only function as elements of healthcare services but also as agents of economic development and pillars of efficiency in the public healthcare system.